Comfort Dolls: Notes for the History of Fabric Toys in Spain - Capellà Simó, Pere (Historia y Memoria de la Educación, 2022)
The Aesthetic and psychoeducational context of the modern era led to the trend of toys made of fabric, which reached Spain during World War I. From then until the end of the century, these transitional objects became an efficient visual support for transmitting social imaginaries. With the objective of diversifying the fields of history of education, from school culture to the culture of childhood in all of its plurality, this article constitutes the first approximation to the history of fabric toys in Spain.